THE CURRENT STATE OF GENETIC AND METABOLIC ENGINEERING OF Geobacillus BACTERIA AIMED AT THE PRODUCTION OF ETHANOL AND ORGANIC ACIDS - A. S. Rozanov; I. A. Meshcheryakova; S. V. Shekhovtsov; S. E. Peltek (Вавиловский журнал генетики и селекции)
Thermophilic bacteria are extensively used in biotechnology. Species of the genus Geobacillus rank among the most promising ones. Current methods of the genetic and metabolic engineering of these microorganisms are considered. Examples of their use in various branches of biotechnology are presented.